Underground tanks of glass-reinforced plastics (GRP). Horizontal cylindrical tanks for the non-pressure storage of liquid petroleum based fuels. Transport, handling, storage and installation of single wall tanks Part 2, (15th December 1997) - British Standards Institution,
No abstract available